L’arbre de la Raison – La fabrique d’un motif pictural au début du XIXe siècle - Mezinski, Zenon (RACAR : Revue d'art canadienne / Canadian Art Review, 2015)
The nineteenth century witnessed the rise of a specialized body of writing that ascribed a central place to the tree as object of knowledge and that contributed to the development of a pictorial motif that I call the “tree of Reason” (“l’arbre de la Raison”). Appearing in Europe in the early nineteenth century, the first “landscape lessons” aimed at beginner artists and amateurs rested on a new pedagogy that promised the reader and student quick results, regardless of their artistic talent. Their approach was based on an extreme form of rationalisation and simplification, which followed from the theoretical and aesthetic principles of Neoclassicism. Behind the word “landscape” (paysage) found in the titles of these successful manuals lay the motif of the tree, which constituted their main subject. This article begins with an examination of Principes raisonnés du paysage, published in 1804 by Nicolas-Alphonse Michel Mandevare, and analyzes the drawing method that it proposes. Regarded as the result of a construction, of an arrangement of its different parts, this “tree of Reason” highlights the end of a big artistic cycle, which was paradoxically to have little influence on the tenets of modern landscape that took hold in the 1830s. This rationalistic and reasoned practice thus ended in an impasse, in which both tree and landscape became petrified in a set of codified rules and references.